Association of Bipolaris and Drechslera Species with Bipolaris Leaf Blight (BPLB) Infected Wheat Leaves - Momtaz, Mst Selina; Shamsi, Shamim; Dey, Tapan Kumar (Journal of Bangladesh Academy of Sciences, 2019)
Five species of Bipolaris and two species of Drechslera associated with leaf blight disease of wheat (Triticum aestivum L.) have been described. The associated fungi were Bipolaris cynodontis (Marig.) Shoemaker, B. oryzae (Breda De Haan) Shoemaker, B. sorokiniana (Sacc.) Shoemaker, B. tetramera (Mckinney) Shoemaker, B. victoriae (Meehan & Murphy) Shoemaker, Drechslera dematioidea (Bub. & Wrob.) Subram. & Jain and D. hawaiiensis (Bugnicourt) ex M.B. Ellis; Subram. & Jain. Journal of Bangladesh Academy of Sciences, Vol. 43, No. 1, 11-16, 2019